Feeding in the Devonian antiarch placoderm fishes: a study based upon morphofunctional analysis of jaws. (November 2022) - Lebedev, Oleg A.; Johanson, Zerina; Kuznetsov, Alexander N.; Tsessarsky, Alekey; Trinajstic, Kate; Isakhodzayev, Farkhad B.
Abstract: Antiarch placoderm fishes were an abundant component of the Middle Paleozoic vertebrate assemblages. Despite a large number of known taxa and specimens, the morphology and function of the skeletal elements of their jaws is inadequately known. Because of this, questions regarding their feeding modes and their roles in the trophic webs remain open. We present a skeletomuscular model of the antiarch jaw apparatus with an attempt to reconstruct its potential biomechanical function. The position of the upper jaw suborbital bones within the plane of the ventral side of the fish armor is suggested to represent the natural "mouth closed" position. During mouth opening, the suborbitals rotated rostrally with simultaneous depression and inward rotation of the infragnathals. The ball-and-socket jaw articulation might ensure this combined movement. Recently described lower jaw elements of Livnolepis zadonica (Obrucheva, 1983 ) and Bothriolepis sp. from the Upper Devonian (lower Famennian) of Central Russia demonstrating very deep and porous blades of the oral division of the infragnathals queried the structure of these bones in other antiarchs. Observed porosity reflects intense vascularization to supply blood to a connective tissue underlying a supposed keratinous sheath, which protected and strengthened the jaws, as well as made possible scraping tough food objects, such as thallus algae, from the substrate. Having evolved during the Silurian in the Pan-Cathaysian zoogeographical province, antiarchs migrated to Gondwana during the Emsian and later to Euramerica during the Eifelian. Supposedly, antiarchs became the first macrophytophagous vertebrates occupying the trophic level of primary consumers during the late Silurian–Early Devonian. This event diversified the only previously existing predator–prey interrelationships between filter-feeding agnathans and predatory gnathostomes.